ANALISIS TINGKAT KESEHATAN MENGGUNAKAN METODE RGEC PADA PT. BANK SYARIAH INDONESIA, Tbk TAHUN 2020 – 2022 - Malik, Tio Maulana; Kurniati, Edy Dwi; Supraptini, Nunuk (BISECER (Business Economic Entrepreneurship), 2024)
There are several factors that can influence the financial performance of sharia banks, So it is necessary to assess the health level of Islamic banks to determine whether the condition of a bank is healthy or unhealthy (Gultom, et al., 2022). This research aims to determine the level of bank health by applying the method RGEC at PT. Bank Syariah Indonesia, Tbk in 2020-2022.In this research, the RGEC This method includes several factors, the first is the riskprofile factor, the ratios used are net performing financing (NPF) and financing to debt ratio (FDR). The second factor is good corporate governance (GCG), which is good corporate governance. The third factor is earnings (profitability), the ratios used are return on assets (ROA), return of equity (ROE) and operating expenses to operating income (BOPO). The final factor in the RGEC method is the capital factor, using the capital adequacy ratio (CAR) as an assessment of the bank's health.In 2020 PT. Bank Syariah Indonesia, Tbk obtained an NPF of 1.72%, which means it was ranked 1st. FDR is 73.84%, which means it is ranked 1st. GCG gets a score of 2. ROA is 1.29%, which means it is ranked 2nd. ROE is 4.56%, which means it is ranked 2rd. BOPOgot 84%, which means it was ranked 1st. CAR gets 18.24%, which means it is ranked 1st. The results of the research show that the assessment of the health level of PT. Bank Syariah Indonesia, Tbk in 2020 obtained a score of 88.57%, which was ranked 1st. In 2021 PT. Bank Syariah Indonesia, Tbk obtained an NPF of 2.93%, which means it was ranked 1st. FDR is 72.69%, which means it is ranked 1st. GCG gets a score of 2. ROA is 1.53%, which means it is ranked 2nd. ROE is 12.11%, which means it is ranked 3rd. BOPO got 80%, which means it was ranked 1st. CAR got 22.09%, which means it was ranked 1st. The research results show that the 2021 health level assessment obtained a score of 88.57%, which is ranked 1st. In 2022 PT. Bank Syariah Indonesia, Tbk obtained an NPF of 2.24%, which means it was ranked 2nd. FDR is 78.50%, which means it is ranked 2nd. GCG gets a score of 2. ROA is 1.85%, which means it is ranked 1st. ROE is 12.87%, which means it is ranked 2nd. BOPO got 76%, which means it was ranked 1st. CAR got 20.29%, which means it was ranked 1st. The results of the research show that the assessment of the bank's health level in 2022 received a score of 88.57%, which is ranked 1st. This means that it can be concluded that from 2020-2022 PT. Bank Syariah Indonesia, Tbk received a very good assessment, obtaining a score of 88.57%, Composite Rank 1 with a very healthy predicate..